Reducing the Symptomatology of Panic Disorder: The Effects of a Yoga Program Alone and in Combination with Cognitive-Behavioral Therapy - Vorkapic, Camila Ferreira; Rangé, Bernard (Frontiers in Psychiatry, 2014)
Introduction: Yoga is a holistic system of different mind–body practices that can be used to improve mental and physical health. It has been shown to reduce perceived stress and anxiety as well as improve mood and quality of life. Research documenting the therapeutic benefits of yoga has grown progressively for the past decades and now includes controlled trials on a variety of mental health conditions such as depression, anxiety, and panic disorder. Objectives: The primary goal of this study was to investigate the effects of yoga in patients suffering from panic disorder. We aimed at observing the efficacy of yoga techniques on reducing the symptomatology of panic disorder (anxiety and agoraphobia), compared to a combined intervention of yoga and psychotherapy. Method: Twenty subjects previously diagnosed with panic disorder were selected. Subjects were randomly assigned to both experimental groups: Group 1 (G1-Yoga: 10 subjects) attended yoga classes and Group 2 (G2-CBT + Yoga: 10 subjects) participated in a combined intervention of yoga practice followed by a cognitive-behavioral therapy (CBT) session. Both interventions occurred weekly for 100 min and lasted 2 months. Subjects were evaluated two times during the study: pre-test and post-test. Psychometric tools included the Beck Anxiety Inventory (BAI), Hamilton Anxiety Rating Scale (HAM-A), The Panic Beliefs Inventory (PBI), and Body Sensations Questionnaire (BSQ). Results: Statistical analysis showed significant reductions in anxiety levels associated with panic disorder (G1: BAI – p = 0.035, HAM-A – p = 0.000; G2: BAI – p = 0.002, HAM-A – p = 0.000), panic-related beliefs (G1: PBI – p = 0.000; G2: PBI – p = 0.000) and panic-related body sensations (G1: BSQ – p = 0.000; G2: BSQ – p = 0.000) both in G1 and G2. However, the combination of yoga and CBT (G2) showed even further reductions in all observed parameters (mean values). Conclusion: This study observed significant improvement in panic symptomatology following both the practice of yoga and the combination of yoga and psychotherapy. While contemplative techniques such as yoga promote a general change in dealing with private events, CBT teaches how to modify irrational beliefs and specific cognitive distortions. The results observed in G2 might indicate that the techniques complemented each other, increasing the intervention efficacy. These findings are in agreement with many investigations found in the literature which observed improvements in different mental health parameters after the practice of contemplative techniques alone or combined to psychotherapy. Future research joining psychological and physiological variables could help better elucidate the mechanisms through which mind-body practices work to improve mental health.